1983
DOI: 10.1111/j.1523-536x.1983.tb01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Death: Grief Support for Families

Abstract: Adequate support for parents whose baby dies requires close listening to the parents themselves, and familiarity with other successful programs of helping parents with grief: Interviews with 24 parents who lost their babies revealed what they found to be supportive or damaging behavior on the part of caregivers. Parents wanted doctors and nurses to acknowledge their feelings of shock, guilt, and grieL to recognize the importance of parents' memories of the birth and the baby, and to help parents sharpen the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…Syracuse, NY: Syracuse University, 1995; Cacciatore, in press.). 17,22 Three described parents who were resentful about inadequate pain control during labor, and five reported parents who regretted feeling sedated during delivery. Although sedatives are not a recommended treatment for grief reactions, a surprisingly high 41% of parents interviewed in a 1994 study reported that their physicians had prescribed such medications.…”
Section: Resultsmentioning
confidence: 99%
“…Syracuse, NY: Syracuse University, 1995; Cacciatore, in press.). 17,22 Three described parents who were resentful about inadequate pain control during labor, and five reported parents who regretted feeling sedated during delivery. Although sedatives are not a recommended treatment for grief reactions, a surprisingly high 41% of parents interviewed in a 1994 study reported that their physicians had prescribed such medications.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses who gave parents permission to cry, who used humor appropriately and who seemed to go out of their way to spend extra time with the family were viewed as particularly supportive. 16,30,44 Many parents felt their nurses had given them special attention; some identified this as extra emotional or spiritual support whereas others saw it as additional time or care beyond the usual tasks. 17,20 Several parents commented that when caregivers were themselves tearful, it felt honest and genuine and the tears seemed appropriate.…”
Section: Interactions Helpful To Parentsmentioning
confidence: 99%
“…Parents frequently described nurses bending hospital policies to accommodate them, such as expanding visiting hours or allowing children on the wards. 16,20,24,44 Families appreciated nurses who took care to provide special photos or mementoes of the baby or who helped them create memories of their baby. 17,18 Nurses who attended to the physical needs of mothers after delivery, including small tasks such as brushing a mother's hair or holding her hand, were also seen as supportive.…”
Section: Interactions Helpful To Parentsmentioning
confidence: 99%
See 2 more Smart Citations